2019
DOI: 10.1111/codi.14659
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive transanal surgery is safe after incomplete polypectomy of low risk T1 rectal cancer: a systematic review

Abstract: Aim In patients who have undergone a polypectomy of a malignant rectal polyp without histopathological risk factors other than an involved or unclear resection margin, additional local excision is often performed. Evidence to support this approach is lacking. The aim of this systematic review and meta‐analysis was to determine the outcome in terms of local recurrence, disease‐free survival (DFS) and overall survival (OS) of additional local excision following incomplete polypectomy for low risk T1 rectal cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Our findings suggest that, in selected patients, long-term oncological outcomes after endoscopic excision of the polyp by EMR or ESD are no different to current clinical practice in a centre where all three options are available at expert level and describes the dilemmas encountered at MDT. Several previous studies have examined oncological outcomes after local excision and radical surgery [3,[11][12][13]15]. However, most of these studies have included both colonic and rectal cancer making it difficult to draw conclusions about rectal cancer specifically [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings suggest that, in selected patients, long-term oncological outcomes after endoscopic excision of the polyp by EMR or ESD are no different to current clinical practice in a centre where all three options are available at expert level and describes the dilemmas encountered at MDT. Several previous studies have examined oncological outcomes after local excision and radical surgery [3,[11][12][13]15]. However, most of these studies have included both colonic and rectal cancer making it difficult to draw conclusions about rectal cancer specifically [13].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, with the development of endoscopic mucosal resection (EMR) and endoscopic submucosal dissection (ESD), it is now possible to resect more advanced polyps and early cancers safely [7][8][9][10]. Both techniques are increasingly used for early rectal cancer and a number of studies have demonstrated that it is also safe to perform a TEM/ TAMIS after a polyp resection [11][12][13][14][15].…”
mentioning
confidence: 99%
“…Because rectal cancer patients have no specific clinical symptoms in the early stage, with the progression of disease, patients will suffer from different degrees of constipation and diarrhea. Nowadays, rectal cancer diseases are mostly detected by proctoscope and digital rectal examination, and rectal cancer masses are characterized by rapid growth, uneven surface, and hard texture [12][13][14]. Surgical resection is currently one of the most commonly used methods in the clinical treatment of rectal cancer, but because most patients are diagnosed in the middle and late stage, the clinical efficacy of surgical resection is not ideal, with high postoperative recurrence rates.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, benign disease (polyps without submucosal invasion or excisional biopsy for masses of uncertain malignant potential) or uT1 malignant disease with favorable tumor characteristics (no lymphovascular invasion, perineural invasion, or mucinous component) are appropriate [7,8] . TAMIS also has a role in local excision following incomplete polypectomy to provide negative margins, as well as in cases of palliative resection in patients who are unfit for total mesorectal excision (TME) [9] . The quality of local excision appears to be equally achieved as that by TEM [10] .…”
Section: Indications For Tamismentioning
confidence: 99%